A comparison of two systems for group housing of gestating sows - effects on productivity, removal, and treatments - Kaisa Ryytty Sylvén; Torun Wallgren; Pontus Almerheim; Lena Eliasson Selling; Magdalena Jacobson; Per Wallgren (Porcine Health Management)
Abstract Background Group housing of sows has been extensively studied since the EU banned gestation crating. Well-managed group-housing promotes sow welfare, but the impact varies based on factors such as feeding, group characteristics, and environmental features. Adequate floor space, particularly directly post-mixing, is crucial for social interactions, natural behaviours, and to reduce injuries caused by aggression. The aim of this study was to compare two group-housing systems for gestating sows with respect to productivity, treatment frequency, and removal of sows. Both systems were static but differed in space allowance, quantity of enrichment material and feeding management. System I comprised of large sized pens with deep litter straw bedding, housing in total 40 sows, and System II of smaller sized pens with permanent access to straw, housing 8 to 10 sows. Results The mean parity number was 3.1 ± 1.3 in both groups. Sows housed in System I with large groups (n = 40) in large pens with deep litter straw gave birth to 16.8 ± 0.33 (Least Squares Means, LSM) piglets, compared to 15.4 ± 0.31 (LSM) for sows in System II kept in smaller groups (n = 8–10) in smaller pens (p = 0.0005). Medical treatments of sows were more frequent (p < 0.001) in System II. The incidence of replacement of sows was comparable in both systems, and there was a high occurrence of sows becoming pregnant during the subsequent insemination in both groups. Conclusions This study indicated that sows kept in larger groups provided with a larger floor space (a total area of 156 m2, corresponding to 3.9 m2 per sow) and housed on deep straw had a higher number of liveborn and weaned piglets and lower incidence of antibiotic treatments than sows with less floor space (a total area of 24.5 m2, corresponding to 2.5–3.1 m2 per sow) and less bedding/manipulable material.